Implementasi Pendidikan Karakter Dalam Kitab Irsyad Al-‘Ibad Represif Degradasi Moral Remaja di Pondok Pesantren - Saputra, Doni (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Writing this thesis contains about the implementation of character education in irsyadul 'ibad repressive moral degradation of adolescents in the tahfidhil Qur'an Islamic boarding school Lilbanaat. The purposes of this research are: (1) To find out how the concept of character education in the book al-irsyad al-'ibad. (2) To find out how the implementation of character education in the book al-irsyad al-'ibad repressive moral degradation of adolescents in the tahfidhil qur'an Islamic boarding school. (3) To find out the inhibiting factors for the implementation of character education in the book al-irsyad al-'ibad in the tahfidhil qur'an lilbanat Islamic boarding school. In writing, the researcher uses qualitative research methods. The data sources used are primary data sources and secondary data sources. Then the approach taken is through observation, interviews, and documentation. The data analysis process is carried out by data reduction, data presentation and drawing conclusions. Then the final conclusions of this thesis are: (1) the concept of character education in the book al-irsyad al-'ibad is this is the science of taswuf which aims to shape human beings to the path of goodness. seen little by little, (2) The implementation of character education in the book of al-Irsyad al-'ibad repressive moral degradation of adolescents at the Tahfidhil Qur'an Lilbanat Islamic boarding school as follows: (a) respecting or glorifying the ulama', (b) respecting guests, (c) sunnah prayer dluha, (d) sunnah prayer of dawn, (e) reading of istighfar, (f) reading of takbir, (g) tahmid, and tasbih, (h) reading of letters al-Ikhlas, al-Falaq, and an- Nas, (3) The inhibiting factor in improving character education mostly experienced in PPTQ is due to factors from the students themselves, so there needs to be awareness from the students themselves.